Special edition using Microsoft Office PowerPoint 2007 - Rutledge, Patrice-Anne (Que, 2007)
Special Edition Using Microsoft® Office PowerPoint® 2007 THE ONLY POWERPOINT BOOK YOU NEED We crafted this book to grow with you, providing the reference material you need as you move toward PowerPoint proficiency and use of more advanced features. If you buy only one book on PowerPoint 2007, Special Edition Using Microsoft® Office PowerPoint® 2007 is the only book you need. - Quickly move from learning PowerPoint 2007 basics to creating and delivering polished, dynamic presentations with Microsoft Office's new user interface - Collaborate on presentations using slide libraries, Microsoft Office SharePoint Server 2007, and more - Communicate data in pictures using charts, diagrams, and graphs, including new SmartArt diagrams and enhanced graphics effects - Design sophisticated presentations even faster with themes and custom layouts - Create multimedia presentations using video, sound, pictures, and animation - Publish and deliver your presentations on the Web - Expand the power of PowerPoint with add-ins and third-party tools - Discover the secrets for powerful delivery of your presentation Patrice-Anne Rutledge is a best-selling author of 24 computer and business books, a successful technology journalist, and an expert in business presentations. She has used-and has taught others to use-PowerPoint for more than 10 years, designing presentations for meetings, seminars, trade shows, and worldwide audiences. Special Edition Using Microsoft® Office PowerPoint® 2007 is her fourth book on PowerPoint. Geetesh Bajaj is a Microsoft PowerPoint MVP (Most Valuable Professional) who runs the Web's foremost PowerPoint site at www.indezine.com. He is also author of another best-selling PowerPoint book. Geetesh believes that successful presentations are the sum of various elements as diverse as color, layout, and graphics. Tom Mucciolo, founder and president of MediaNet, is an acclaimed speaker on presentation skills. He is an expert at enhancing the key components of communication, including the message (script), the media (visual design), and the mechanics (delivery). His one-to-one coaching sessions, ranging from basic to advanced, develop individual style and prepare a person for presenting in a very visual world. On the CD-ROM - NXPowerLite - SmartDraw 30-Day Trial Edition - Exclusive cartoon from Mark Anderson (AnderToons) - ActiveSlide Thunder Trial plus examples - Camtasia Studio Trial - Sample presentations - Electronic version of this book in A ...